2002
DOI: 10.1785/0120000604
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Excavation and Recent Rupture History along the Cholame Segment of the San Andreas Fault

Abstract: A paleoseismic study conducted along the Cholame segment of the San Andreas fault provides evidence for three earthquakes and the amount of lateral offset for the most recent event (1857 Fort Tejon earthquake). Excavations at the Las Yeguas (LY4) site include five fault-perpendicular, two parallel, and several handdug trenches. Abruptly truncated sand and silt layers that are not correlative across the fault zone constrain the timing of the penultimate event (L2) between cal. A.D. 1030-1300 and 1390-1460. Vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The larger number of fractures observed in BDT19a and BDT19c is likely due to effects of excavation equipment, which may have overprinted or opened tectonic fractures near the surface. Similar fractures were reported at the LY4 (Young et al, 2002) and Phelan fan (Grant and Sieh, 1993) sites (Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The larger number of fractures observed in BDT19a and BDT19c is likely due to effects of excavation equipment, which may have overprinted or opened tectonic fractures near the surface. Similar fractures were reported at the LY4 (Young et al, 2002) and Phelan fan (Grant and Sieh, 1993) sites (Fig. 1).…”
Section: Discussionsupporting
confidence: 81%
“…At each site, the fractures are generally oriented parallel or en echelon along the fault zone, with less than a few centimeters of opening. The LY4 fractures were hand excavated in a horizontal exposure and their pattern was consistent with a few centimeters of SAF parallel shearing (and not with excavation; Young et al, 2002). The source of LY4 fractures, and their age, remains enigmatic.…”
Section: Discussionmentioning
confidence: 92%
“…Paleoseismic trenching studies provide the only constraint on the slip amplitude and spatial extent of this historical event on the Southern SAF. Earlier studies on the Carrizo segment inferred a fault slip of about 10 m at the surface during the event (26), while recent studies suggested a smaller amount of ~5 m (27,60). However, study based on historical surveys found that large slip of ~11 m is required at greater depths (29).…”
Section: )mentioning
confidence: 98%
“…For the Parkfield segment, repeating M ~6 events have been recorded to occur at similar locations (16,64). Further to the south, the 1857 M w 7.9 Fort Tejon earthquake is well-documented to have ruptured the Cholame, Carrizo, and Mojave segments based on paleoseismic trenching studies and historical surveys (26,27,29,30,60,61,65,66). Prior to 1857, major historical events on the southern SAF are the two earthquakes that occurred adjacent to each other in Dec. 1812, which we denote with a single year and rupture extent.…”
Section: Paleoseismic Records For the San Andreas And San Jacinto Faultsmentioning
confidence: 99%
“…Since Biasi and Weldon's (1994) original application of Bayesian methods to paleoseismic investigations, a number of software packages developed by the archeological community (OxCal, Bcal [Buck et al, 2001]; Bronk-Ramsey [1995]) have been used by paleoseismologists to estimate stratigraphic layer ages and earthquake ages using Bayesian methods (e.g., Fumal, Reymer, et al, 2002;Lindvall et al, 2002;Young et al, 2002). While the implementation of the Bayesian problem differs from Biasi and Weldon's (1994) quasi-explicit solution, the Markov-Chain Monte Carlo (MCMC) methods used by OxCal and Bcal (e.g., BronkRamsey, 1995;Buck et al, 1996) generally produce similar results to those of Biasi and Weldon (1994) in the case that stratigraphic layer ordering is considered (compare solution methods described in Biasi and Weldon [1994] with those described by Buck et al [1996]).…”
Section: Introductionmentioning
confidence: 99%